2022
DOI: 10.1161/jaha.121.023175
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Prediction Models for Severe Complications After Acute Ischemic Stroke: A Study Based on the Stroke Registry of Northwestern Germany

Abstract: Background The treatment of stroke has been undergoing rapid changes. As treatment options progress, prediction of those under risk for complications becomes more important. Available models have, however, frequently been built based on data no longer representative of today’s care, in particular with respect to acute stroke management. Our aim was to build and validate prediction models for 4 clinically important, severe outcomes after stroke. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 49 publications
0
15
1
Order By: Relevance
“…The predictive performance of RFC and GBC models significantly outperformed LRC and MLPC as assessed by the AUC difference. The superior predictive performance of GBC models over classical regression was previously documented in a large study conducted to predict severe complications after acute ischemic stroke ( 8 ). In general, the performance metrics of the best ML models in our study were either better or comparable to previous models developed to predict HT incidence in previous studies taking into consideration differences in the utilized HT definition, study design, ethnicity, and sample size of the study group ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The predictive performance of RFC and GBC models significantly outperformed LRC and MLPC as assessed by the AUC difference. The superior predictive performance of GBC models over classical regression was previously documented in a large study conducted to predict severe complications after acute ischemic stroke ( 8 ). In general, the performance metrics of the best ML models in our study were either better or comparable to previous models developed to predict HT incidence in previous studies taking into consideration differences in the utilized HT definition, study design, ethnicity, and sample size of the study group ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 82%
“…Among the most commonly used supervised ML classifiers are logistic regression classifier (LRC), support vector classifiers (SVC), random forest classifier (RFC), decision tree-based gradient boosting classifier (GBC), and multilayer perceptron classifier (MLPC). Machine learning algorithms were reported to efficiently analyze complex non-linear interactions between variables and were utilized to develop prediction models in a variety of clinical settings ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Age and NIHSS score are the two most commonly used variables employed in sICH prediction. 7,8 In addition, Bonkhoff et al 26 also found that stroke severity (NIHSS score) was the overall most important predictor in their model for predicting severe complications after ischemic stroke including secondary intracerebral hemorrhage. It is consistent with our domain analysis, which showed clinical characteristics (NIHSS score, SBP and DBP) yielded the highest prediction measures in both the Caucasian and Han Chinese samples.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated GIT disturbances in stroke patients such as dysphagia, gastrointestinal bleeding, or constipation ( 17 ). A recent stroke registry study showed that 19.6% of patients experience swallowing problems and indicate dysphagia frequency of 75.4% which is associated with a high risk of death during hospital admissions ( 5 ). Approximately 50% of the dysphagia complications persisted even after hospital discharge ( 4 , 6 , 17 ), causing a persistent burden on patients’ health.…”
Section: Stroke Induces Gastrointestinal Complicationsmentioning
confidence: 99%